Hepatic iron storage in very low birthweight infants after multiple blood transfusions. Issue 2 (1st March 2001) - Ng, P C; Lam, C W K; Lee, C H; To, K F; Fok, T F; Chan, I H S; Wong, E
Abstract : OBJECTIVE: To investigate the effect of multiple blood transfusions on hepatic iron storage in preterm, very low birthweight (VLBW) infants. METHODS: Seventeen VLBW infants who died within the first six months of life and underwent postmortem examination were studied. Serum ferritin, iron, and total iron binding capacity were measured within the week before the infants' death. Liver iron concentration was quantitatively determined by atomic absorption spectrophotometry and semiquantitatively assessed by histochemical liver iron grading. The clinical characteristics and the iron results were compared between infants receiving < 100 ml of blood (group A) and those receiving ⩾ 100 ml (group B). Spearman's correlation coefficient was used to evaluate the relation between the volume of blood transfused and serum/liver iron concentrations. Statistically significant variables associated with liver iron concentration were further subjected to multivariate stepwise regression analysis. RESULTS: Infants in group B had significantly higher serum iron (p < 0.01), serum ferritin (p < 0.01), and liver iron concentration (p < 0.01) than those in group A. The total and net volume of blood transfused were significantly associated with liver iron concentration (p < 0.001, r = 0.86; p < 0.001, r = 0.71 respectively), semiquantitative histochemical liver iron grading (p < 0.001, r = 0.80; p < 0.005, r = 0.71 respectively), and serum ferritin (p < 0.001, r = 0.84; p < 0.01, r = 0.69 respectively). In addition, both liver iron concentration and liver iron grading were found to be significantly associated with serum ferritin (p < 0.001, r = 0.76; p < 0.005, r = 0.68 respectively). Multivariate stepwise regression analysis indicated that the (log) liver iron concentration was significantly associated with the (log) volume of blood transfusion (p < 0.001; regression coefficient 0.39, SE 0.09), after adjustment for gestational age ( R 2 = 0.84). CONCLUSIONS: This study showed a significant positive relation between the volume of blood transfused and the liver iron concentration in preterm VLBW infants. Although the transfusional blood volume correlated closely with the amount of iron deposited in hepatic tissues, clinical manifestations of iron overload were not observed. Carers should be aware of this potential harmful effect before prescribing blood or routine iron supplement to vulnerable preterm infants.